PECULIARITIES OF ASSESSMENT OF INTRINSIC PROTECTABILITY OF WATERBEARING HORIZONS (Proceedings of the YSU C: Geological and Geographical Sciences, 2008)
Problems of assessment of intrinsic protectability of water-bearing horizons on the pattern of Shirak basin are discussed in the paper. Qualitative assessment of water-table horizon protectability is made on the basis of depth to water table, thickness and permeability of impermeable soil in aeration zone. Quantitative assessment of water-table horizon intrinsic protectability is carried out on tracking time of pollutants to water-table (days). Intrinsic protectability of the first from land surface confined aquifer was made on the basis of overlaid impermeable soil’s thickness and relationship between water table and potentiometric levels. Water-table horizon is evaluated as not protected and poorly protected, confined horizon is assessed as tentatively protected and protected.
Keywords: Shirak basin; intrinsic protectability; impermeable soil in aeration zone